Self-Efficacy and Health Promotion: The Roles of Family Health and Health Literacy - Yeşildal, Müjdat; Öztürk, Yunus Emre (UI Scholars Hub, 2026)
Background: Chronic noncommunicable diseases are the leading causes of death globally and in Türkiye, emphasizing the need to explore how individual, familial, and informational factors shape health-promoting behaviors. This study examined whether family health and health literacy sequentially mediate the relationship between general self-efficacy and health-promoting behaviors among adults in Türkiye. Methods: A cross-sectional correlational study was conducted with 1,240 adults in Konya Province, Türkiye, between November and December 2022. Participants completed the Turkish versions of the General Self-Efficacy, Family Health, Health Literacy, and Health-Promoting and Protective Behaviors Scales. Data were analyzed using descriptive statistics, Pearson correlation, and PROCESS macro Model 6 to test the serial mediation model, accounting for both direct and indirect effects. Results: Self-efficacy, family health, and health literacy were significantly and positively associated with health-promoting behaviors (p < 0.001). The serial mediation analysis confirmed that family health and health literacy partially and sequentially mediated the relationship between self-efficacy and HPBs. Notably, the model demonstrated a substantial effect size, explaining 38.4% of the total variance in HPBs. Conclusions: Self-efficacy influences health behaviors both directly and indirectly through its impact on family health and health literacy. Interventions should target both individual motivation and relational and informational support, especially in collectivist contexts such as the one in Türkiye.